Fireproof and stain-resistant composite coating and preparation method thereof
By intercalating MXene nanomaterial with montmorillonite, and preparing spherical composite materials, combined with epoxy resin and other additives, the problems of easy agglomeration and insufficient flame retardant performance of MXene nanomaterials are solved, and the preparation of fire-resistant and stain-resistant composite coatings is realized, and the stability and fire-resistance of the coating are improved.
Patent Information
- Application Number
- CN202411869430.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, MXene nanomaterials are prone to agglomeration in coatings, affecting the performance of the coatings, and their flame retardant properties are not effectively improved, increasing fire safety hazards.
By intercalation with montmorillonite, a special preparation method is used to convert the MXene/montmorillonite composite material from sheet-based to spherical form, and combined with epoxy resin and other additives to prepare a fire-resistant and stain-resistant composite coating.
It effectively improves the stability and flame retardant properties of MXene nanomaterials, improves the stain resistance and fire resistance of the coating, making the coating easier to coat and the appearance of the dry coating smoother.
Smart Images

Figure BDA0005195382110000021 
Figure FDA0005195382100000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, and in particular to a fire-proof and stain-resistant composite coating and a preparation method thereof. Background Art
[0002] In recent years, fire accidents have occurred frequently around the world, causing great casualties, property losses and environmental damage. Fires can be divided into many types, including building fires, forest fires, vehicle fires and industrial fires. Among them, building fires are the most frequent, most important and high-risk type of fire accidents. Building fires often occur in places where people live, work or entertain. Among the many factors that may cause building fires, the most important reason is the use of flammable and combustible building materials. In the field of construction, bamboo and wood materials, polymers and other materials are widely used, but most of them are flammable and can easily cause building fires, thereby increasing fire safety hazards. Therefore, improving the flame retardant properties of bamboo materials, polymers and other materials has always been the focus of academic and industrial circles.
[0003] Two-dimensional transition metal nitride and carbide (MXene) nanomaterials with a lamellar structure are a newly discovered two-dimensional material after graphene. In recent years, they have attracted widespread attention in the fields of materials science, biomedicine, nanotechnology, etc. MXene has good thermal stability, unique lamellar structure, excellent catalytic activity and adjustable chemical properties, and is widely used in the research of flame retardants. However, MXene nanomaterials are easy to agglomerate and have poor stability. Direct application in coatings will affect the performance of coatings, which greatly affects the application of MXene nanomaterials. In order to improve the defects of MXene nanomaterials, MXene is often adjusted by optimizing the synthesis or post-treatment of the MAX phase, but these methods are complex and costly, which is not conducive to industrialization. Summary of the invention
[0004] The object of the present invention is to provide a fire-resistant and stain-resistant composite coating which is simple to prepare and low in cost and a preparation method thereof in view of the deficiencies in the prior art.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention is to provide a fire-resistant and stain-resistant composite coating, which comprises, by weight:
[0007]
[0008] Preferably, the diluent comprises: at least one of diethylene glycol glycidyl ether, ethylene glycol glycidyl ether, hexanediol glycidyl ether, polypropylene glycol diglycidyl ether or polyethylene glycol diglycidyl ether.
[0009] Preferably, the auxiliary agent includes at least one of a curing agent, a coupling agent, a defoaming agent and a leveling agent.
[0010] More preferably, the curing agent includes at least one of dodecanedioic acid, propylene glycol butyl ether, diethylenetriamine, 4,4'-diaminodiphenylmethane, triglycidyl isocyanurate, and β-hydroxyalkylamide.
[0011] More preferably, the defoaming agent includes at least one of dimethyl silicone oil, fatty alcohol polyoxyethylene ether, benzoin, and polyethylene wax.
[0012] More preferably, the leveling agent includes at least one of polydimethylsiloxane, polyamide wax and carboxymethyl cellulose.
[0013] The second aspect of the present invention is to provide a method for preparing the above-mentioned composite coating, the steps comprising:
[0014] S1. Weigh the MXene / montmorillonite composite filler in parts by weight, and ultrasonically disperse it in deionized water to prepare a filler dispersion;
[0015] S2. Weigh the epoxy resin, the diluent and the auxiliary agent according to their weight, put the epoxy resin and part of the diluent into a container for a first stirring treatment, add the filler dispersion and sequentially perform a second stirring treatment and a grinding and dispersion treatment, finally add the remaining diluent and the auxiliary agent, disperse and mix at a high speed to obtain the composite coating.
[0016] Preferably, the preparation steps of the MXene / montmorillonite composite filler include:
[0017] A1. Etching MXene with alkaline solution; dispersing the etched MXene in a montmorillonite solution and performing ultrasonic stirring to obtain a MXene / montmorillonite mixed solution;
[0018] A2. The MXene / montmorillonite mixed solution is subjected to atomization treatment and freeze-drying treatment in sequence to obtain the MXene / montmorillonite composite filler.
[0019] More preferably, the ultrasonic stirring has a power of 200-220 W and a time of 40-60 min.
[0020] Preferably, in step S2, the temperature of the first stirring treatment is 70-80°C, the time is 30-60min, and the speed is 500-800rpm; the temperature of the second stirring treatment is 50-60°C, the time is 1-2h, and the speed is 500-800rpm; the time of the grinding and dispersion is 1-3h; the speed of the high-speed dispersion is 2000-3000rpm, and the time is 10-30min.
[0021] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0022] The present invention uses montmorillonite and MXene nanomaterials for intercalation composite, which effectively improves the problem of easy agglomeration of MXene nanomaterials. At the same time, the flame retardancy of MXene nanomaterials can be significantly improved after being composited with montmorillonite. The present invention uses a special preparation method to transform the MXene / montmorillonite composite material from a lamellar type to a spherical type, and the interior of the spherical composite material is still lamellar, so that the MXene / montmorillonite composite material maintains its original performance while being tightly combined with other raw materials, thereby improving the stain resistance of the coating. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0025] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0026] Example 1
[0027] This embodiment provides a fire-resistant and stain-resistant composite coating and a preparation method thereof, the steps comprising:
[0028] S1. Weigh 7 parts of MXene / montmorillonite composite filler, and ultrasonically disperse them in deionized water to prepare a filler dispersion;
[0029] The preparation method of the MXene / montmorillonite composite filler comprises:
[0030] A1. Etching MXene with alkaline solution; dispersing the etched MXene in montmorillonite solution, and stirring with 220W ultrasonic for 40min to obtain a MXene / montmorillonite mixed solution;
[0031] A2, sequentially subjecting the MXene / montmorillonite mixed solution to atomization treatment and freeze drying treatment to obtain the MXene / montmorillonite composite filler;
[0032] S2. Weigh 60 parts of epoxy resin, 6 parts of ethylene glycol glycidyl ether, 2 parts of diethylenetriamine, 2 parts of dimethyl silicone oil and 3 parts of polydimethylsiloxane, put the epoxy resin and 4 parts of ethylene glycol glycidyl ether into a container, stir at 80°C at a speed of 800 rpm for 30 minutes, add the filler dispersion, stir at 60°C at a speed of 600 rpm for 1 hour, grind and disperse for 1 hour, finally add the remaining ethylene glycol glycidyl ether, diethylenetriamine, dimethyl silicone oil and polydimethylsiloxane, disperse at a high speed of 3000 rpm for 10 minutes and mix to obtain the composite coating.
[0033] Example 2
[0034] This embodiment provides another fire-resistant and stain-resistant composite coating and a preparation method thereof, the steps comprising:
[0035] S1. Weigh 2 parts of MXene / montmorillonite composite filler and disperse them in deionized water by ultrasonic to prepare a filler dispersion;
[0036] The preparation method of the MXene / montmorillonite composite filler comprises:
[0037] A1. Etching MXene with alkaline solution; dispersing the etched MXene in montmorillonite solution, and stirring with 200W ultrasonic for 60min to obtain a MXene / montmorillonite mixed solution;
[0038] A2, sequentially subjecting the MXene / montmorillonite mixed solution to atomization treatment and freeze drying treatment to obtain the MXene / montmorillonite composite filler;
[0039] S2. Weigh 50 parts of epoxy resin, 10 parts of polyethylene glycol diglycidyl ether, 2 parts of dodecanedioic acid, 3 parts of diethylenetriamine, 2 parts of fatty alcohol polyoxyethylene ether, 3 parts of polydimethylsiloxane and 3 parts of carboxymethyl cellulose, put the epoxy resin and 8 parts of polyethylene glycol diglycidyl ether into a container, stir at 700 rpm for 50 min at 70°C, add the filler dispersion, stir at 600 rpm for 1 h at 50°C, grind and disperse for 2 h, finally add the remaining polyethylene glycol diglycidyl ether, dodecanedioic acid, diethylenetriamine, fatty alcohol polyoxyethylene ether, polydimethylsiloxane and carboxymethyl cellulose, disperse at 3000 rpm for 10 min and mix to obtain the composite coating.
[0040] Example 3
[0041] This embodiment provides another fire-resistant and stain-resistant composite coating and a preparation method thereof, the steps comprising:
[0042] S1. Weigh 5 parts of MXene / montmorillonite composite filler and ultrasonically disperse them in deionized water to prepare a filler dispersion;
[0043] The preparation method of the MXene / montmorillonite composite filler comprises:
[0044] A1. Etching MXene with alkaline solution; dispersing the etched MXene in montmorillonite solution, and stirring with 220W ultrasonic for 60min to obtain a MXene / montmorillonite mixed solution;
[0045] A2, sequentially subjecting the MXene / montmorillonite mixed solution to atomization treatment and freeze drying treatment to obtain the MXene / montmorillonite composite filler;
[0046] S2. Weigh 40 parts of epoxy resin, 8 parts of ethylene glycol glycidyl ether, 5 parts of diethylenetriamine, 6 parts of dimethyl silicone oil and 6 parts of polyamide wax, put the epoxy resin and 6 parts of ethylene glycol glycidyl ether into a container, stir at 80°C at a speed of 800 rpm for 30 min, add the filler dispersion, stir at 60°C at a speed of 600 rpm for 1 h, grind and disperse for 1 h, finally add the remaining ethylene glycol glycidyl ether, diethylenetriamine, dimethyl silicone oil and polyamide wax, disperse at a high speed of 3000 rpm for 10 min and mix to obtain the composite coating.
[0047] Comparative Example 1
[0048] This comparative example provides a composite coating and a preparation method thereof. The filler adopts conventional MXene material, and the rest is the same as Example 1.
[0049] Comparative Example 2
[0050] This comparative example provides another composite coating and a preparation method thereof, wherein montmorillonite is used as a filler, and the rest is the same as in Example 1.
[0051] Comparative Example 3
[0052] This comparative example provides another composite coating and a preparation method thereof, wherein quartz sand is used as a filler, and the rest is the same as in Example 1.
[0053] Detection Example
[0054] The performance of the composite coatings of Examples 1-3 and Comparative Examples 1-3 was tested respectively.
[0055] The DSA10-MK2 contact angle meter was used to test the water contact angle of the coating with a smooth surface. Each coating was tested three times and the middle value was taken. The QHQ pencil hardness tester, KX-DB-501 impact testing machine and QFH adhesion tester were used to test the impact strength, pencil hardness and adhesion of the coating in accordance with GB / T1732-2020, GB / T 6739-2022 and GB / T9286-2021.
[0056] The test results are shown in Table 1;
[0057] Table 1
[0058] Water contact angle Adhesion hardness Impact resistance Limiting oxygen index Example 1 116.2° Level 0 3H 50cm 47.2% Example 2 109.4° Level 0 3H 50cm 41.9% Example 3 114.7° Level 0 3H 50cm 42.0% Comparative Example 1 70.9° Level 2 2H 40cm 31.5% Comparative Example 2 64.5° Level 2 H 40cm 28.7% Comparative Example 3 63.1° Level 3 H 30cm 24.1%
[0059] Comparative Examples 1-3 all use lamellar fillers, and the water contact angle of the obtained coating is relatively low, indicating that corrosive media, water molecules, and dirt are easy to penetrate; Examples 1-3 use spherical MXene / montmorillonite composite fillers, which are more tightly combined with other raw materials, and the water contact angle of the obtained coating is significantly increased, indicating that the coating is hydrophobic and effectively prevents the adsorption of corrosive media, water molecules, and dirt; in addition, the limiting oxygen index of the coating obtained in Examples 1-3 is also higher than that of Comparative Examples 1-3, which shows that the flame retardant performance of the composite filler is better than that of the single-component filler.
[0060] In summary, the present invention uses montmorillonite and MXene nanomaterials for intercalation composite, which effectively improves the problem of easy agglomeration of MXene nanomaterials. At the same time, the flame retardancy of MXene nanomaterials can be significantly improved after being composited with montmorillonite. The present invention uses a special preparation method to transform the MXene / montmorillonite composite material from a lamellar type to a spherical type, and the interior of the spherical composite material is still lamellar, so that the MXene / montmorillonite composite material maintains its original performance while being better dispersed in the coating, thereby making the coating easier to apply and the appearance of the coating after drying is smoother.
[0061] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A fire-resistant and stain-resistant composite coating, characterized in that: By weight, the components include:
2. The composite coating according to claim 1, characterized in that: The diluent includes at least one of diethylene glycol glycidyl ether, ethylene glycol glycidyl ether, hexanediol glycidyl ether, polypropylene glycol diglycidyl ether or polyethylene glycol diglycidyl ether.
3. The composite coating according to claim 1, characterized in that: The auxiliary agent includes at least one of a curing agent, a coupling agent, a defoaming agent and a leveling agent.
4. The composite coating according to claim 3, characterized in that: The curing agent comprises at least one of dodecanedioic acid, propylene glycol butyl ether, diethylenetriamine, 4,4'-diaminodiphenylmethane, triglycidyl isocyanurate, and β-hydroxyalkylamide.
5. The composite coating according to claim 3, characterized in that: The defoaming agent comprises at least one of dimethyl silicone oil, fatty alcohol polyoxyethylene ether, benzoin and polyethylene wax.
6. The composite coating according to claim 3, characterized in that: The leveling agent includes at least one of polydimethylsiloxane, polyamide wax and carboxymethyl cellulose.
7. A method for preparing a composite coating according to any one of claims 1 to 6, characterized in that the steps include: S1. Weigh the MXene / montmorillonite composite filler in parts by weight, and ultrasonically disperse it in deionized water to prepare a filler dispersion; S2. Weigh the epoxy resin, the diluent and the auxiliary agent according to their weight, put the epoxy resin and part of the diluent into a container for a first stirring treatment, add the filler dispersion and sequentially perform a second stirring treatment and a grinding and dispersion treatment, finally add the remaining diluent and the auxiliary agent, disperse and mix at a high speed to obtain the composite coating.
8. The preparation method according to claim 7, characterized in that: The preparation steps of the MXene / montmorillonite composite filler include: A1. Etching MXene with alkaline solution; dispersing the etched MXene in a montmorillonite solution and performing ultrasonic stirring to obtain a MXene / montmorillonite mixed solution; A2. The MXene / montmorillonite mixed solution is subjected to atomization treatment and freeze-drying treatment in sequence to obtain the MXene / montmorillonite composite filler.
9. The preparation method according to claim 8, characterized in that: The power of the ultrasonic stirring is 200-220W, and the time is 40-60min.
10. The preparation method according to claim 7, characterized in that: In step S2, the temperature of the first stirring treatment is 70-80°C, the time is 30-60min, and the speed is 500-800rpm; the temperature of the second stirring treatment is 50-60°C, the time is 1-2h, and the speed is 500-800rpm; the time of the grinding and dispersion is 1-3h; the speed of the high-speed dispersion is 2000-3000rpm, and the time is 10-30min.
Citation Information
Patent Citations
MXene modified epoxy anticorrosive paint and preparation method thereof
CN115926581A
Zirconium dioxide / MXene composite filler modified epoxy resin anticorrosive paint as well as preparation method and application thereof
CN116987429A
Hydrotalcite two-dimensional material-based composite nanofiller and anticorrosive paint
CN118931229A
Preparation method of modified MXene / epoxy resin composite anticorrosive paint
CN119119825A